Bimodal anti‐glioma mechanisms of cilengitide demonstrated by novel invasive glioma models. Issue 2 (19th September 2012) - Onishi, Manabu; Ichikawa, Tomotsugu; Kurozumi, Kazuhiko; Fujii, Kentaro; Yoshida, Koichi; Inoue, Satoshi; Michiue, Hiroyuki; Chiocca, E. Antonio; Kaur, Balveen; Date, Isao
<x xml:space="preserve">Abstract</x> Integrins are expressed in tumor cells and tumor endothelial cells, and likely play important roles in glioma angiogenesis and invasion. We investigated the anti‐glioma mechanisms of cilengitide (EMD121974), an αvβ3 integrin inhibitor, utilizing the novel invasive glioma models, J3T‐1 and J3T‐2. Immunohistochemical staining of cells in culture and brain tumors in rats revealed positive αvβ3 integrin expression in J3T‐2 cells and tumor endothelial cells, but not in J3T‐1 cells. Established J3T‐1 and J3T‐2 orthotopic gliomas in athymic rats were treated with cilengitide or solvent. J3T‐1 gliomas showed perivascular tumor cluster formation and angiogenesis, while J3T‐2 gliomas showed diffuse single‐cell infiltration without obvious angiogenesis. Cilengitide treatment resulted in a significantly decreased diameter of the J3T‐1 tumor vessel clusters and its core vessels when compared with controls, while an anti‐invasive effect was shown in the J3T‐2 glioma with a significant reduction of diffuse cell infiltration around the tumor center. The survival of cilengitide‐treated mice harboring J3T‐1 tumors was significantly longer than that of control animals (median survival: 57.5 days and 31.8 days, respectively, P < 0.005), while cilengitide had no effect on the survival of mice with J3T‐2 tumors (median survival: 48.9 days and 48.5, P = 0.69). Our results indicate that cilengitide exerts a phenotypic anti‐tumor effect by inhibiting angiogenesis and glioma cell invasion. These two mechanisms are clearly shown by the experimental treatment of two different animal invasive glioma models.